Clinical Profile and Outcome of Renal Replacement Therapy in a Pediatric Intensive Care Unit of a Tertiary Care Hospital - Javaid, Muhammad Sulman; Basheer, Faisal; Ateeq, Saad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the clinical profile and outcome of patients undergoing renal replacement therapy at a pediatric intensive care unit (ICU) of a tertiary care teaching hospital of Pakistan. Study Design: Prospective longitudinal study. Place and Duration of Study: Pediatric ICU, Pak Emiratse Military Hospital (PEMH) Rawalpindi, from Jan to Jun 2018. Methodology: This study was conducted on 60 patients of acute kidney injury undergoing renal replacement therapy in the pediatric ICU of MH RWP during the study period. Outcomes were correlated with the recovery of patients. Results: A total of 60 patients admitted in pediatric intensive care unit were put on renal replacement therapy in the study duration time. Male to female ratio was 2.1:1. Acute gastroenteritis was the commonest underlying medical disorder among the target population followed by sepsis. Mean age of patients put on renal replacement therapy was 4.13 ± 4.925 years. Most of the patients were put on renal replacement therapy due toelectrolyte imbalance. Out of 60 patients, 26 (43.3%) recovered, 09 (15%) were transformed into chronic kidney disease, 08 (13.3%) into end stage renal disease and 17 (28.3%) died. Female gender and use of peritoneal dialysis were the factors associated with non-recovery in our sample population. Conclusion: Acute gastroenteritis and sepsis have been the common illnesses and conditions that can give rise to acute kidney injury and require the renal replacement therapy in a pediatric intensive care unit. Management of critically ill children involving the renal replacement therapy is an integral part of pediatric critical care medicine.